2021
DOI: 10.1093/ehjqcco/qcab058
|View full text |Cite
|
Sign up to set email alerts
|

Global representation of heart failure clinical trial leaders, collaborators, and enrolled participants: a bibliometric review 2000–20

Abstract: Background The geographic representation of investigators and participants in heart failure (HF) randomized clinical trials (RCTs) may not reflect the global burden of disease. Aims We assessed the geographic diversity of RCT leaders and explored associations with geographic representation of enrolled participants among impactful HF RCTs. Methods and Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 31 publications
0
33
0
Order By: Relevance
“…The limited organization and follow-up required to conduct pragmatic trials also offers the potential to conduct robust research in regions with limited research infrastructure and trained personnel, which are grossly under-represented in trials relative to disease prevalence 1 . For example, the SSaSS trial 62 , which was conducted in 600 rural villages in China (~21,000 participants), demonstrated that the use of a salt substitute (75% sodium chloride and 25% potassium chloride) reduced the risk of stroke compared with regular salt (100% sodium chloride).…”
Section: Comparisons Across Precis-2 Domainsmentioning
confidence: 99%
See 2 more Smart Citations
“…The limited organization and follow-up required to conduct pragmatic trials also offers the potential to conduct robust research in regions with limited research infrastructure and trained personnel, which are grossly under-represented in trials relative to disease prevalence 1 . For example, the SSaSS trial 62 , which was conducted in 600 rural villages in China (~21,000 participants), demonstrated that the use of a salt substitute (75% sodium chloride and 25% potassium chloride) reduced the risk of stroke compared with regular salt (100% sodium chloride).…”
Section: Comparisons Across Precis-2 Domainsmentioning
confidence: 99%
“…However, as investigators, regulators, policy-makers and patients become more reliant on evidence-based results to support clinical care, the failure of contemporary RCTs to address the entire spectrum of clinically relevant questions is becoming increasingly apparent. Most cardiovascular RCTs conducted to date have been primarily ‘explanatory’ in nature; that is, they were designed to study the efficacy of interventions in ‘optimized’ conditions, with highly selected patient populations and protocolized assessments of safety and efficacy 1 , 2 . Although such trial designs increase internal validity, they provide limited information about the effectiveness of the intervention in the great variety of scenarios that exist in routine clinical practice but were not represented in the RCT, thereby compromising the generalizability of the trial results 1 , 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trial populations, however, tend to be much more homogeneous in demographics and comorbidities than patients in clinical settings. 4–7…”
mentioning
confidence: 99%
“…Trial populations, however, tend to be much more homogeneous in demographics and comorbidities than patients in clinical settings. [4][5][6][7] There are concerns that race and ethnicity data may be inadequately reported in RCTs, but reporting is essential to understanding the interplay between race and ethnicity and treatment outcomes both in clinical and research settings. 7 Race and ethnicity are heterogenous social constructs that may influence the estimated treatment effect in RCTs due to variations in healthcare system engagement, quality of care, and socioeconomic factors.…”
mentioning
confidence: 99%